Hope for Help-Seeking: A Positive Psychology Perspective of Psychological Help-Seeking Intentions ψ. (February 2017) - McDermott, Ryon C.; Cheng, Hsiu-Lan; Wong, Joel; Booth, Nathan; Jones, Zachary; Sevig, Todd
In the present study, we used multigroup structural equation modeling in a sample of college students ( N = 2, 461) to examine ethnic and gender differences in the connections between dispositonal hope and intentions to seek psychological help from formal and informal sources. In a personal-emotional problem scenario, we found a robust positive relationship between hope and intentions to seek help from informal sources, but no association for formal sources. In a suicidal thoughts scenario, hope was positively associated with intentions to seek both informal and formal psychological help. Results of exploratory moderation analyses indicated that the model was invariant across non-Latino White students and Asian American students, as well as across men and women. These findings address critical gaps in the hope and help-seeking literature, and suggest that increasing college students' dispositional hope may provide a unique positive psychology-focused avenue for increasing help-seeking intentions, even within underserved populations.